Cryptococcal meningitis post-covid-19 infection: Immunomodulation, a double-edged sword - Hilal W Abdessamad; Michel Achkar; Amal Al Zoghbi; Mohamad Fleifel; Abdul Rahman Ousta; Ahmad Kassar; Nadia L Samaha; Rita Nemr; Anna Farra; Jacques E Mokhbat; Rola Husni (Journal of Infection in Developing Countries)
Cryptococcal meningitis is an opportunistic infection associated with altered immunity. Immunomodulatory agent use in severe coronavirus disease 2019 (COVID-19) may predispose such infections. Here, we present a 75-year-old male patient who presented with fever and altered general status after severe COVID-19 infection and developed cryptococcal meningitis. Opportunistic infection may arise from the use of immunomodulation in severe COVID-19, especially in the elderly population. This article describes the case and extensively reviews cryptococcal disease post-COVID-19 literature, highlighting the risk from immunosuppressive treatment.